A Study on the Effectiveness of Homoeopathic Constitutional Medicine in the Management of Non-Alcoholic Fatty Liver Disease (Advancements in Homeopathic Research, 2025)
NAFLD is an important cause of liver disease in India.  During the past century, dramatic modifications in  lifestyle have radically changed the health priorities  in most areas of the world, owing to a growing  incidence of non-communicable disease. Fatty liver  has earlier often been related with excessive alcohol  consumption. During the past 20 years, the interest in  fatty liver occurring in non-drinkers i.e. non-alcoholic  fatty liver disease (NAFLD) has raised quickly. Methods A prospective experimental study design  without control group.Patients will be collected  from the In-patient and Out-patient Departments,  Peripheral Centres, Rural Health Camps and  Medical Camps conducted by Vinayaka Mission’s  Homoeopathic Medical College and Hospital Result This study provides evidence to say that, there  is significant reduction in the Non-alcoholic fatty  liver disease after giving homoeopathic constitutional  medicine
Keywords: Homeopathy; liver; NAFLD; constitutional medicine; life style disorder